"It takes skills to take a car": Perceptual and procedural expertise in carjacking. (January 2015) - Topalli, Volkan; Jacques, Scott; Wright, Richard
Abstract: This article explores the crucial role played by criminal expertise in carjacking, a violent street offense that exhibits characteristics of both car theft and robbery. Specifically, it describes the manner in which an offender's perceptual skills (aimed at discerning the suitability of a carjacking target) and procedural skills (aimed at enacting the carjacking offense itself) relate to one another in a process emanating from the interacting characteristics of the vehicle, driver, environment, and offender. The core assumption of this perspective is that carjacking requires considerable skill to identify an appropriate offense opportunity and carry out the same. This contradicts a prevailing notion within the criminological literature that offending is a largely unskilled enterprise. Drawing on ethnographic data both original and in previous research we demonstrate this not to be the case.